The "turn" to spirituality - C. Kourie (Acta Theologica)
The term “spirituality” is difficult to define, given the equivocal meanings attributed to it, and the tendency to equate this phenomenon with “piety” or “otherworldliness”. Such an approach is far too narrow, and does not take into account that “spirituality” needs to be seen in a much wider context. Spirituality refers to the raison-d’être of one’s existence, the meaning and values to which one ascribes. Thus everyone embodies a spirituality, be it nihilistic, materialistic, humanistic, or religious. There are diverse spiritualities, each one culture-specific, expressing its own historical, sociological, theological, linguistic and philosophical orientation. Post-patriarchal and telluric, contemporary spirituality affects all areas of society, including the business world, education, health care, the arts, ecology, politics, religion and particularly the academy, where new programmes in spirituality are attracting a large number of students. The new surge of interest in spirituality is a force for personal and societal transformation.